2014
DOI: 10.1002/prot.24607
|View full text |Cite
|
Sign up to set email alerts
|

Binding site multiplicity with fatty acid ligands: Implications for the regulation of PKR kinase autophosphorylation with palmitate

Abstract: Saturated long chain-free fatty acids (FFAs), especially palmitate, have been implicated in apoptosis by inhibiting the activity of PKR (double-stranded RNA-dependent protein kinase). We recently found evidence that palmitate interacts directly with the kinase domain of PKR, subsequently inhibiting the autophosphorylation of PKR. To investigate the interactions of palmitate with PKR and its effects on PKR autophosphorylation, we performed extensive unbiased MD simulations combined with biochemical and biophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…It is unclear how PKR is activated in this condition, as no requirement for dsRNA or PACT has been demonstrated. However, it was shown that PKR could be activated by free fatty acids (FFA); at high concentrations, the long unsaturated FFA palmitate can interact with the kinase domain of PKR to inhibit kinase activity [224]. It was also shown that PKR activation is dependent on interaction with phosphorylated TRBP, and shows that inhibition of TRBP can lead to increased glucose sensitivity [225].…”
Section: Metabolic Disease-associated Inflammation-potential Involvem...mentioning
confidence: 99%
“…It is unclear how PKR is activated in this condition, as no requirement for dsRNA or PACT has been demonstrated. However, it was shown that PKR could be activated by free fatty acids (FFA); at high concentrations, the long unsaturated FFA palmitate can interact with the kinase domain of PKR to inhibit kinase activity [224]. It was also shown that PKR activation is dependent on interaction with phosphorylated TRBP, and shows that inhibition of TRBP can lead to increased glucose sensitivity [225].…”
Section: Metabolic Disease-associated Inflammation-potential Involvem...mentioning
confidence: 99%
“…Thus, defects in eIF2 are potentially fatal ( 17 , 18 ). These are currently known to be associated with a wide range of disorders, such as delayed sensitivity, contact dermatitis, impaired glucose tolerance, insulin resistance, Alzheimer's disease, myelodysplastic syndromes, and different types of cancers (breast cancer, leukemia, melanoma, hepatocellular carcinoma, and colon cancer) ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%